Premature Infants Conceived with Assisted Reproductive Technology: An Analysis of Infant Morbidity, Compared with Infants Conceived Naturally - Scala, Melissa; Berg, Jennifer; Keszler, Martin; Abubakar, Kabir (American Journal of Perinatology, 2019)
Objective This article evaluates the morbidity of infants born via assisted reproductive technology (ART) compared with matched naturally conceived infants.Study Design This is a retrospective review of maternal and infant data among inborn infants conceived via ART and matched control infants born at 30 to 34 weeks' gestational age (GA) between 2006 and 2012. Data were analyzed using paired t-test or Wilcoxo–Mann–Whitney test for continuous and Fisher's exact test for categorical variables. p-Value of < 0.05 was considered significant.Result Of 120 study infants, 60 were conceived via ART and 60 naturally. Control infants were matched for GA, gender, race, and multiple gestations. ART infants required more respiratory support and took longer to reach full feeds compared with control infants.Conclusion Infants born via ART are physiologically more immature with more intensive care needs than naturally conceived infants of similar gestation, potentially increasing health care costs. This immaturity should be considered when planning early delivery in these pregnancies.
Keywords: assisted reproductive technology; neonatal outcomes; preterm infant; neonatal intensive care unit